Identification of Isocitrate Dehydrogenase 2 (IDH2) Mutation in Carotid Body Paraganglioma - Lang, Fengchao; Jha, Abhishek; Meuter, Leah; Pacak, Karel; Yang, Chunzhang (Frontiers in Endocrinology, 2021)
Carotid body paragangliomas (PGLs) are rare neuroendocrine tumors that develop within the adventitia of the medial aspect of the carotid bifurcation. Carotid body PGLs comprise about 65% of head and neck paragangliomas, however, their genetic background remains elusive. In the present study, we report one case of carotid body PGL with a somatic mutation in the gene encoding isocitrate dehydrogenase 2 (IDH2). The missense mutation in IDH2 resulted in R172G amino acid substitution, which exhibits neomorphic activity and production of D-2-hydroxyglutarate.